The View of Islamic Economic on Risk Management Strategies for Wet Fish Traders - Rabiah, Rabiah; Haeran, Haeran (Zabags International Journal of Economy, 2024)
This research aims to identify the risk management strategies implemented by wet fish traders in Sungai Cemara Village, Sadu District and analyze the Islamic economic view of the risk management strategies implemented by wet fish traders. This research approach is a descriptive qualitative research approach. Participants in this research were fishermen and buyers of wet fish in the village. In obtaining data in the field, observation, interviews and documentation are used. The research results obtained are: first, the risk management strategy implemented by wet fish traders, namely always maintaining the quality of the goods to be sold so that customers do not feel disappointed, lowering the selling price and transferring it to other traders and increasing the number of stones. ice or store in the refrigerator. Second, the Islamic economic view of the risk management strategy implemented by wet fish traders does not contain transactions that are prohibited in Islam, for example swearing falsely when selling their merchandise. Apart from that, there are no elements of false promotion or oaths made by fish sellers to be convincing.